(untitled) (BIRDEM Medical Journal, 2020)
Swyer syndrome with complete gonadal dysgenesis is associated with an absence of testicular differentiation in a phenotypic female with a 46, XY karyotype. The diagnosis is usually made at adolescence when primary amenorrhea is investigated. Here is an interesting case report of 18-year-old unmarried girl, who presented with primary amenorrhea and non-development of breasts. Her body built was musculin with broad shoulders, prominent Adam’s apple and deep voice. Examination of her secondary sexual charaistisctcs revealed no breast development, absent axillary hair and sparse pubic hairs with female type of external genitalia. Laboratoryanalyses revealed serum follicle-stimulating hormone and luteinizing hormone levels compatible with hypergonodotropichypogonadism. Pelvicultrasonography showed an infantile uterus and streak gonads. Chromosome analysis revealed 46, XYkaryotype. Laparoscopic removal of streak gonads was done as there is a risk of gonadoblastoma in such cases. The patient was started on hormonal replacement therapy. Swyersyndrome results mainly due to mutation in certain genes such as SRY gene, which leads to failure of development of testis. Birdem Med J 2020; 10(2): 130-132